The Role of AI Literacy in Reducing Academic Anxiety and Enhancing Self-Regulated Learning Among University Students - Khateeb, Linda Ahmad (Journal of Ecohumanism, 2024)
This study aimed to investigate how artificial intelligence (AI) literacy can alleviate academic anxiety and facilitate self-regulated learning among students at universities. The study was of a descriptive correlational type; the study sample included 80 undergraduate students in Al Esra University who had utilized artificial intelligence tools as learning media, and the study covered students who had used the artificial intelligence tools for academic purposes. Data was gathered with a questionnaire that included measuring the AI literacy, academic anxiety, and self-regulated learning. Data were analyzed by means, standard deviations, and Pearson's correlation coefficients. Pearson's correlation coefficient was employed for data analysis. The results indicated that the AI literacy and self-regulated learning level among students are high, and the academic anxiety level is moderate. The result showed that there was a negative relationship between AI literacy and academic anxiety, which is statistically significant, meaning the respondents with higher AI literacy experienced lower academic anxiety. The results showed that there was a statistically significant positive relationship between AI literacy and self-regulated learning, and that artificially intelligent literacy at a high level means that students have good goal setting, planning, monitoring, strategy use, and self-evaluation. The data in this study indicate that AI literacy is a significant psychological and educational resource that can contribute to student confidence and independence in doing academic tasks supported by AI. The research proposes that training university students should be given in effective prompting, critical evaluation of AIG information, promoting an ethical framework for AI usage, and fostering autonomous approaches or strategies for utilizing AIG information.